Volume 4: 18th Design for Manufacturing and the Life Cycle Conference; 2013 ASME/IEEE International Conference on Mechatronic A 2013
DOI: 10.1115/detc2013-13006
|View full text |Cite
|
Sign up to set email alerts
|

Effective Reverse Engineering of Qualitative Design Knowledge: A Case Study of Aerospace Pylon Design

Abstract: Global collaboration is now a key for enterprises to rapidly achieve their worldwide successes. During the rapid expansion of their business, many challenges are emerging, e.g., novice training, knowledge transferring, intellectual property (IP) protection. This paper presented an effective approach for gaining new knowledge in a design project through reverse engineering by using Environment Based Design (EBD) methodology. The case study used in this paper was designed to demonstrate how design knowledge can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Environment-based design (EBD) [24,25] is a systematic design methodology under research and development at Concordia University by Professor Yong Zeng. EBD has also reported positive research attempts in aircraft design [26,27] and potential integrations with design methodologies such as TRIZ, and axiomatic design [28]. Mavris and Pinon [20], and Price, et al [19] demonstrate that SE exhibits strong similarities with the aircraft design process, as both build on decomposition, synthesis, and verification to achieve successful systems.…”
Section: Methodsmentioning
confidence: 99%
“…Environment-based design (EBD) [24,25] is a systematic design methodology under research and development at Concordia University by Professor Yong Zeng. EBD has also reported positive research attempts in aircraft design [26,27] and potential integrations with design methodologies such as TRIZ, and axiomatic design [28]. Mavris and Pinon [20], and Price, et al [19] demonstrate that SE exhibits strong similarities with the aircraft design process, as both build on decomposition, synthesis, and verification to achieve successful systems.…”
Section: Methodsmentioning
confidence: 99%
“…The experts worked independently to evaluate the final conceptual design document. The details of the case study can be found in (Tan et al, 2013).…”
Section: Case Studymentioning
confidence: 99%
“…The lifecycle of the pylon interface includes manufacture, transportation, assembly, sales, maintenance, and disposal. The relevant environment components can be found in (Tan et al, 2013). Q7 How to install it?…”
Section: Information Searchmentioning
confidence: 99%
See 1 more Smart Citation